Strategi Komunikasi Bisnis Islam: (Studi pada Usaha Mandiri Mutiara Bunda Yayasan Cahaya Mutiara Bandung) - Suhendi; Tantan Guntana (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Business competition today is inevitable in order to facilitate to meet the needs and convenience of consumers. Business As part of muamalah, Islam has a clear shari'a in carrying out its economic activities as instructed in the Qur'an applied by the Prophet Muhammad SAW. Sharia-based business is part of the da'wah that must be done by every Muslim as an economic actor. Mandiri Mutiara Bunda business shows the form of business communication in its economic activities conducted on the basis of islamic economic rules. This is the purpose of this research is to know the form of Islamic business communication in UMMB business in facilitating and improving the welfare of its members as consumers. Using qualitative methods of phenomenological perspective, the results of this study show that there are several forms of Islamic business communication, among others: verbal, nonverbal, face-to-face, and media communication contained in UMMB business.